Hepatitis C hospitalizations in Spain and impact of new curative antiviral therapies - Ramos-Rincón, José-Manuel; Pinargote-Celorio, Héctor; de Mendoza, Carmen; Ramos-Belinchón, Clara; Barreiro, Pablo; Gómez-Gallego, Felix; Corral, Octavio Jorge; Soriano, Vicente (Journal of Viral Hepatitis, 2023)
Chronic hepatitis C virus (HCV) infection is major cause of decompensated cirrhosis and liver cancer. The advent of curative new antiviral therapies since year 2015 has dramatically improved the prognosis of HCV patients. The real-life clinical benefits at country level of these therapies have not yet been assessed. This is a retrospective study of all hospitalizations in Spain including HCV as diagnosis using the Spanish National Registry of Hospital Discharges. Information was retrieved from 1997 to 2019. From 81,482,509 nationwide hospital admissions recorded during the study period, 1,057,582 (1.29%) included HCV as diagnosis. The median age of HCV hospitalized patients was 54 years old. Males accounted for 63.2% of cases. Most HCV admissions recorded chronic hepatitis C whereas acute hepatitis C was reported in less than 3%. In-hospital death occurred in 6.4% of HCV admissions. Coinfection with HIV or hepatitis B virus was seen in 14.8% and 6.4%, respectively. Patients hospitalized with HIV-HCV coinfection represented 14.8% of cases and were on average 17 years younger than HCV-monoinfected individuals. The rate of HCV hospitalizations significantly increased until 2005, and then stabilized for one decade. A significant reduction was noticed since 2015. However, whereas the proportion of HCV-associated hepatic decompensation events declined since then, liver cancer diagnoses increased. In conclusion, hospital admissions of HCV individuals significantly declined in Spain since 2015 following a wide prescription of new oral direct-acting antivirals. This reduction was primarily driven by a fall of hepatic decompensation events whereas HCV-related liver cancer continues rising.
Keywords: antiviral therapy; cirrhosis; hepatitis C; HIV; hospitalizations; liver cancer; JCR; Scopus